2013
DOI: 10.1002/ggge.20102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 hydrate formation on seismic wave velocities of fine‐grained sediments

Abstract: [1] This study examines the effect of gas hydrate formation on seismic wave velocities of fine-grained sediments. Synthesis of gas hydrates in fine-grained sediments has proved to be challenging, and how hydrate formation would affect the seismic wave velocities and stiffness of clay-rich sediments has not yet been fully understood. In this study, CO 2 hydrate was synthesized in remolded and partially water-saturated clayey silt sediments that were originally cored from a hydrate occurrence region in the Ulleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Through the comparison with model predictions such as those of Dvorkin et al (2000), it was found that this relationship depends on the hydrate morphology, such as grain coating, cementing, pore-filling, and sediment frame component (or loadbearing) within the pore space (M. Lee et al, 1996;Berge et al, 1999;Reister, 2003;Yun et al, 2005;Priest et al, 2009;J. Lee et al, 2010;Hu et al, 2010, Li et al, 2011Best et al, 2013;Kim et al, 2013a). This suggests that the P-wave velocity obtained from logging and seismic surveys can be used to estimate the in situ hydrate saturation if the hydrate morphology in actual reservoirs is revealed.…”
Section: Introductionmentioning
confidence: 95%
“…Through the comparison with model predictions such as those of Dvorkin et al (2000), it was found that this relationship depends on the hydrate morphology, such as grain coating, cementing, pore-filling, and sediment frame component (or loadbearing) within the pore space (M. Lee et al, 1996;Berge et al, 1999;Reister, 2003;Yun et al, 2005;Priest et al, 2009;J. Lee et al, 2010;Hu et al, 2010, Li et al, 2011Best et al, 2013;Kim et al, 2013a). This suggests that the P-wave velocity obtained from logging and seismic surveys can be used to estimate the in situ hydrate saturation if the hydrate morphology in actual reservoirs is revealed.…”
Section: Introductionmentioning
confidence: 95%
“…The second and third rounds of X‐ray scanning were performed 115 h (∼5 days, Stage 2) and 213 h (∼9 days, Stage 3) after the onset of hydrate formation. These hydrate‐forming conditions are applicable to the excess gas method, which has been widely employed to synthesize gas hydrate samples in laboratory settings [e.g., Ebinuma et al ., ; Masui et al ., ; Waite et al ., ; Winters et al ., ; Priest et al ., ; Jung and Santamarina , ; Kim et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Controlled laboratory experiments on synthesized hydrate‐bearing sediments have been performed in the past by some researchers to relate the pore saturation of gas hydrates to the physical properties of sediments. A number of routes to synthesize gas hydrate‐bearing sediment samples in the laboratory have been explored, including the ice seed method [e.g., Stern et al ., ; Waite et al ., ; Priest et al ., ; Hyodo et al ., ], excess gas method [e.g., Waite et al ., ; Winters et al ., ; Kim et al ., ], excess water method [ Priest et al ., ], and a method using dissolved gas or THF [e.g., Spangenberg et al ., ; Yun et al ., ; Lee et al ., ; Kwon and Cho , ; Lee et al ., , b]. Among these methods, forming gas hydrates from partially water‐saturated sediments, referred to as the excess gas method, has been widely adopted because of its simplicity and the ability to control the hydrate saturation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations